Experimental Snap Loading of Synthetic Ropes - C.M. Hennessey; N.J. Pearson; R.H. Plaut (Shock and Vibration)
Large tensile forces, known as snap loads, can occur when a slack rope becomes taut. Such forces may damage the rope or masses connected to it. Experiments are described in which one end of a rope is attached to the top of a drop tower and the bottom end is attached to a weight. The weight is raised to a certain height and then released. The force at the top of the rope and the acceleration of the weight are recorded during the first snap load that occurs. Repeated drop tests are performed on each rope. The effects of the type of rope, drop height, drop weight, whether the rope has been subjected to static precycling, and the number of previous dynamic tests are examined. A mathematical model is proposed for the rope force as a function of the displacement and velocity of the weight.